An Online Growth Mindset Intervention in a Sample of Rural Adolescent Girls - Burnette, Jeni L. (Br J Educ Psychol, 2017)
BACKGROUND: Students living in rural areas of the United States exhibit lower levels of educational attainment than their suburban counterparts. Innovative interventions are needed to close this educational achievement gap. AIMS: We investigated if an online growth mindset intervention could be leveraged to promote academic outcomes. SAMPLE: We tested the mindset intervention in a sample of 222 10(th) grade adolescent girls (M age=15.2; 38% White, 25% Black, 29% Hispanic) from four rural, low-income high schools in the Southeastern United States. METHODS: We conducted a randomized controlled trial to test the efficacy the growth mindset intervention, relative to a sexual health program. We used random sampling and allocation procedures to assign girls to either the mindset intervention (n=115) or an attention-matched control program (n=107). We assessed participants at pretest, immediate posttest, and four-month follow-up. RESULTS: Relative to the control condition, students assigned to the mindset intervention reported stronger growth mindsets at immediate posttest and four-month follow-up. Although the intervention did not have a total effect on academic attitudes or grades, it indirectly increased motivation to learn, learning efficacy and grades via the shifts in growth mindsets. CONCLUSIONS: Results indicate that this intervention is a promising method to encourage growth mindsets in rural adolescent girls.